2022
DOI: 10.1021/acs.est.1c08522
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Soup Foods in Plastic Packaging Are Associated with Phthalate Body Burden and Expression of Inflammatory mRNAs: A Dietary Intervention Study

Abstract: Plastic packaging material is widely used to package high-temperature soup food in China, but this combination might lead to increased exposure to phthalates. The health effects and potential biological mechanisms have not been well studied. This study aimed to examine urinary phthalate metabolites and the expression of inflammatory cytokines in the blood before, during, and after a "plastic-packaged high-temperature soup food" dietary intervention in healthy adults. The results showed that compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In contrast, Zhang et al. (2022) reported increases in the levels of some plastics (MBP, MIBP, and total phthalates) with the consumption in high‐temperature of plastic‐packaged instant soups, and this possible source of phthalate exposure is plastic bags. As the contact temperature in packaging materials, the degrees such as refrigerator and environment temperature can be applied, as well as high temperatures can be applied for foods cooked in their packaging due to the cooking temperature or processes such as washing and sterilization applied to the material.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, Zhang et al. (2022) reported increases in the levels of some plastics (MBP, MIBP, and total phthalates) with the consumption in high‐temperature of plastic‐packaged instant soups, and this possible source of phthalate exposure is plastic bags. As the contact temperature in packaging materials, the degrees such as refrigerator and environment temperature can be applied, as well as high temperatures can be applied for foods cooked in their packaging due to the cooking temperature or processes such as washing and sterilization applied to the material.…”
Section: Resultsmentioning
confidence: 92%
“…In this diet intervention study, the mean concentrations of MMP, MBP, MIBP, and total phthalate metabolites increased significantly when participants began to eat high‐temperature soup foods packaged in plastic bags, suggesting that this may be due to ingestion of these compounds from plastic food bags. Previous studies had shown that plastic (polyethylene and polyethylene terephthalate) packaging materials contain phthalates as plasticizers and that some phthalates in packaging can pass into foods (Zhang et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…However, some are considered endocrine disruptors and can interfere with hormonal regulation . High molecular weight phthalates (>250 Da; ester side-chain lengths of five or more carbons) are employed as plasticizers in the production of polyvinyl chloride plastics and are found in a variety of products, such as food contact materials, building and construction materials (e.g., vinyl flooring, floor tiles, wall coverings, and furniture upholstery), medical devices (tubing, catheters, blood/dialysis bags), and toys. , Low-molecular-weight phthalates (<250 Da; ester side-chain lengths of one to four carbons) are used as solubilizing agents in the formulation of cosmetics and personal care products (e.g., fragrances) and as coatings of some pharmaceuticals . Despite some regulations in Europe, recent birth cohorts and biomonitoring studies show that phthalate exposure is still widespread, with more than 90% of the European population showing detectable concentrations in urine. , In addition, newer phthalates such as bis­(2-propylheptyl) phthalate (DPHP) and the nonphthalate substitute 1,2-cyclohexane dicarboxylic acid diisononyl ester (DINCH) have recently entered the market, showing increasing concentrations in humans over time. , Since these new chemicals have a similar structure to those they replace and could potentially exert deleterious effects, , there is a need for continuous biomonitoring and surveillance. , …”
Section: Introductionmentioning
confidence: 99%